Hazard identification risk assessment and risk control in medical divice manufacturing company during pandemic outbreak / Khairil Anuar Mohammad Pakri - Khairil Anuar, Mohammad Pakri (2022)
The coronavirus, known as COVID-19, started in December of 2019. It started in Wuhan, China, then started spreading around the world till it became a global pandemic. Many people around the world are affected not only in terms of health but also in the economy due to COVID-19. Many industries are facing issues with operating their businesses during a pandemic. Because of a lack of resources, particularly manpower, industry is unable to function normally. They still need to operate the plant to fulfill customer demand. Due to the limitations that industry is facing in order to run a business during a pandemic outbreak, there will be new hazards from manufacturing activities. Lack of skilled workers, attendance issues due to COVID-19, employee’s motivation, and workplace configuration to meet COVID-19 Standard Operating Procedure (SOP) regulated by National Security Council (NSC) becomes a limitation for industries. Details of hazard assessment are required to review past activities and processes in each department of an organization during a pandemic outbreak. Risk analysis needs to be performed immediately once a hazard is identified to find an effective control measure to prevent any unexpected incident from happening. Instead of controlling the spread of COVID-19 in the workplace, industries still need to focus on preventing accidents and occupational health issues to ensure employees come to work safe and healthy. Every employee must be aware of the hazards in their workplace and understand how to overcome the hazards using the control measures discovered during the risk assessment. Employees must be trained on how to work within the new norm in order to protect their safety and health. Even during pandemic season, incidents can be avoided if a proactive assessment is performed to identify new hazards and effective control measures. Assessment needs to be effective and comprehensive in order to cover every angle and situation of a pandemic. The risk assessment needs to be conducted regularly based on the pandemic situation. An industry can operate smoothly if an effective assessment has been conducted. It can minimize the limitations due to a pandemic outbreak. Support from each employee and management is important to ensure it can be done effectively. All countries are facing the same pandemic situation. The only difference is how they manage it, either proactively or not. Proactive countries will accelerate their growth and improve their economies when their industries can operate normally while meeting safety and health standards. From the study, the COVID-19 pandemic had an impact on a medical company's device manufacturing. It can be measured by using the Hazard Identification Risk Assessment and Risk Control method to indicate the level of risk rating for a company operating during the COVID-19 outbreak. Employees' perception of COVID-19 can also be evaluated, and most of them respond that the COVID-19 pandemic has an impact on their daily routine in medical device manufacturing companies.